(untitled) (Conferencea, 2022)
Teachers of English as a foreign language (EFL) encourage students to take a more active role in the oral activities in the classroom through different strategies. This study examines the use of picture descriptions as a strategy to develop and enhance communication skills among students. Pictures are all around us everyday, in the street, at work, at home and even in our leisure time, so why not in the classroom as well? They are enjoyable, they set the scene or context, they inform us, they interest us, and they are a key resource.